2008
DOI: 10.1897/07-294.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the toxicity of copper and zinc salts to wheat in 14 soils

Abstract: Interest is mounting in developing and utilizing soil-specific soil quality guidelines. This requires quantifying the effects that soil physicochemical properties have on various ecotoxicological endpoints, including phytotoxicity. To this end, 14 agricultural soils from Australia with differing soil properties were spiked with copper (Cu) and zinc (Zn) salts and used to conduct 21-d plant growth inhibition tests using wheat (Triticum aestivum L.) in pot trials. The toxicity of Cu and Zn was similar with 10% e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…However, the environmental risks posed by metals are not only a function of their overall presence in soils, but also of their chemical speciation. There have been a number of studies into the effects of metal toxicity on plants (Jolanta and Stanislaw, 2004;Daoust et al, 2006;Lock et al, 2007a;Warne et al, 2008;Papazoglou, 2011). For example, Rooney et al (2007) reported that soil cation exchange capacity was the best single predictor for the median effective concentration (EC50) of added nickel (Ni) and the EC50 ranged from 52 to 1929 mg kg -1 and from 17 to 920 mg kg -1 in tests on barley and tomato plants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the environmental risks posed by metals are not only a function of their overall presence in soils, but also of their chemical speciation. There have been a number of studies into the effects of metal toxicity on plants (Jolanta and Stanislaw, 2004;Daoust et al, 2006;Lock et al, 2007a;Warne et al, 2008;Papazoglou, 2011). For example, Rooney et al (2007) reported that soil cation exchange capacity was the best single predictor for the median effective concentration (EC50) of added nickel (Ni) and the EC50 ranged from 52 to 1929 mg kg -1 and from 17 to 920 mg kg -1 in tests on barley and tomato plants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of Zn found in contaminated soils frequently exceed the limits required to be as a nutrient and may cause phytotoxicity. Zn concentrations in the range of 150-300 mg/kg have been measured in polluted soils (Devries et al 2002;Warne et al 2008). High levels of Zn in soil inhibit many metabolic functions of plants, resulting in retarded growth and cell senescence.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these limitations, normalization relationships could play a crucial role in risk and hazard assessment (Li et al, 2011;Warne et al, 2008), as they can provide estimates of the toxicity of Pb toward soil nitrification in soils when experimentally derived values are lacking. They could also be used to normalize toxicity for use in deriving soil quality guidelines (Li et al, 2010;Warne et al, 2008).…”
Section: Limitations and Advantages Of The Normalization Relationshipsmentioning
confidence: 99%
“…They could also be used to normalize toxicity for use in deriving soil quality guidelines (Li et al, 2010;Warne et al, 2008). The soil quality guidelines could be derived for soil nitrification using the relationships and could be obtained for other soil microbial processes for which there are no similar relationships by simply normalizing the data using the gradient.…”
Section: Limitations and Advantages Of The Normalization Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation